Solar based EV Charging Station - Yede Suraj,; Wable Kiran,; Sankpal Sagar,; Kharade Ravindra,; Dr. Divekar S. N, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
An electric vehicle is a new and upcoming technology and power sector that have many benefits in terms of economic and environmental. This study presents a comprehensive review and evaluation of various types of electric vehicles and its associated equipment in particular battery charger and charging station. A comparison is made on the commercial and prototype electric vehicles in terms of electric range, battery size, charger power and charging time. The various types of charging stations and standards used for charging electric vehicles have been outlined and the impact of electric vehicle charging on utility distribution system is also discussed. The infrastructure element that provides the crucial link between an Electric Vehicle (EV) with a depleted battery and the electrical source that will recharge those batteries is the Electric Vehicle Supply Equipment or EVSE. This report provides a review of the current and emerging EVSE technologies and an assessment of the common codes and standards associated with EVSE. The report also evaluates the barriers and challenges of deploying an expanded.
Keywords: Battery Charger; Charging Station; Electric Vehicle; Standards